Cryonics: Science or Religion - Dein, Simon (Journal of religion and health, 2022)
Cryonics involves the low-temperature freezing of human corpses in the hope that they will one day be reanimated. Its advocates see it as a medical treatment but as in any medical procedure, this presupposes some scientific evidence. This paper examines the scientific basis of this technology and argues that cryonics is based upon assertions which have never been (and potentially can never be empirically demonstrated) scientifically. After providing a general overview of cryogenic preservation, I discuss how advocates of this technology have conceptualized death and more specifically their notion of information-theoretic death. I conclude that cryonics is based upon a naive faith rather than upon science. It does what David Chidester (2005) calls ‘religious work,’ even if it is not explicitly religious. It offers transcendence over death.